Pengaruh E-Marketing terhadap Minat Berwisata di Wisata Pantai Mangrove Kampung Nipah Kecamatan Perbaungan Kabupaten Serdang Bedagai - Sitorus, Agnes; Aramita, Finta (Economics, Business and Management Science Journal, 2025)
This study aims to find out and analyze the influence of e-marketing (website marketing, social media marketing, content marketing, and influencer marketing) on tourism interest in tourists who visit the Mangrove Beach Tourism Object in Kampung Nipah, Serdang Bedagai Regency. This type of research uses a quantitative descriptive method. The data was obtained from a sample of 95 respondents who were visitors to the Mangrove Beach Tourism Object in Kampung Nipah. Sampling was done using hair sampling techniques. Data collection was carried out through the distribution of questionnaires to visiting tourists. The results of the study show that Website Marketing and Influencer Marketing have a positive and significant effect on tourism interest in Mangrove Beach Tourism in Kampung Nipah, while Social Media Marketing and Content Marketing do not show a significant influence. Simultaneously, e-marketing explains 56.5% of the influence on tourist interest. Therefore, tourism managers need to optimize Website Marketing with interesting information and improve Influencer Marketing strategies. Social Media Marketing and Content Marketing also need to be strengthened with interactive and informative content. The results of this study can be a reference in the development of a more effective e-marketing strategy.